THE INFLUENCE OF SCHOOL PRINCIPALS' ACADEMIC SUPERVISION AND ACHIEVEMENT MOTIVATION ON TEACHER WORK CULTURE - SHAFRIDA, Aina (Journal of Education and Leadership in Education, 2023)
The main objective of this study is to analyze the direct influence of the principal's academic supervision on the teacher's work culture, analyze the direct influence of achievement motivation on the teacher's work culture and analyze the direct influence of the principal's academic supervision on the achievement motivation of public high school teachers in Sukmajaya District. This research uses quantitative approach method. The population in the study amounted to 160 public high school teachers in Sukmajaya sub-district. The sampling technique in this study used purposive sampling techniques and used the Slovin formula with an error rate of 5%, so that a sample of 99 teachers was obtained. The data collection in this study used a questionnaire with a Likert scale. Data testing and analysis using SPSS 25. The results of this study showed that the p-value on the Academic Supervision variable of 0.000<0.05 was smaller than 0.05. This means that Academic Supervision has a positive and significant effect on Teacher Work Culture. If Academic Supervision increases, the Teacher's Work Culture will also increase or vice versa, if the Academic Supervision decreases, the Teacher's Work Culture will also decrease. The p-value result on the Achievement Motivation variable of 0.000<0.05 is less than 0.05. This means that Achievement Motivation has a positive and significant effect on Teacher Work Culture. The p-value result on the Academic Supervision variable of 0.000<0.05 is smaller than 0.05. This means that Academic Supervision has a positive and significant effect on Achievement Motivation.